Swimrun: An emerging new endurance sport - Lepers, R.; Li, F.-X.; Stapley, P. J. (Movement & Sport Sciences - Science & Motricité, 2018)
The swimrun is a new endurance team-sport based on two persons swimming and running alternatively through open water and mostly trails. The aim of this study was to analyse participation and performance trends for males, females and mixed duo team at the ÖTILLÖ Swimrun race (10 km open-water swimming and 65 km trail running). During the 2012-2016 period, the mean total time performance of the best athletes at the ÖTILLÖ Swimrun decreased significantly by 17 min/year for males, 40 min/year for mixed and 59 min/year for females duo, respectively. The difference in performance between the best males and females duo (26 ± 15%) was significantly greater compared to the difference between males and mixed duo (12 ± 8%). The number of swimrun races organized across the world has dramatically increased these last years and will probably continue to grow up in the future. Swimrun athletes are still not very experienced, thus both improvements in performance and reduction in sex difference are expected in the next decade.